Surface deposits and intracellular concentration of atmospheric particles in foliage of urban forests in the Valley of Mexico - Luz Amelia Sánchez-Landero; Griselda Benítez-Badillo; Wendy Sangabriel-Conde; Gerardo Alvarado-Castillo; Elio Guarionex Lagunes-Diaz (Trees, Forests and People, 2024)
Foliage of urban vegetation can be used as a bioindicator of air pollution, including heavy metals. We measured surface and intracellular concentration of copper, zinc, lead, nickel, chromium, cobalt and cadmium in Fraxinus uhdei leaves from three urban forests of the Metropolitan Area of the Valley of Mexico (ZMVM) during the four seasons of the year and assessed its correlation with distance to nearest roads; we also compared obtained concentrations with the local atmospheric monitoring network. We performed a two-factor experimental design: factor forest with three levels (Naucalli Park, Forests and Tlalpan) and factor season with four levels, to analyze spatio-temporal differences in heavy metal concentration. Fifteen Fraxinus uhdei trees were selected per site and a foliage sample was taken. A t-test was applied for comparisons between deposits, while an analysis of variance and Tukey's test was used to compare between seasons and forest. Relationship between surface concentrations and distance to the streets surrounding the forests was obtained using the Stepwise method. The obtained results indicate that there are higher concentrations superficially than intracellular in all metals analyzed, except for nickel. Copper was highest in Parque Naucalli, lead, nickel, chromium and cadmium in Bosques Chapultepec and zinc in Bosques Tlalpan. Highest concentrations occurred in summer for copper, zinc, nickel and chromium and in winter for lead and cadmium. We found that the surface concentration of copper, zinc, lead and cadmium in the foliage is higher when trees are closer to avenues. Our research indicates that trees can be valuable bioindicators for air pollution, as they not only mirror the diverse pollution sources but also provide insights into pollutant exposure based on proximity to those sources.